Coxiella burnetii vascular graft infection - Von Segesser Ludwig; Moulin Alexandre; Raoult Didier; Franciolli Mario; Senn Laurence; Calandra Thierry; Greub Gilbert (BMC Infectious Diseases, 2005)
Abstract Background Coxiella burnetii, the causative agent of Q fever, may cause culture-negative vascular graft infections. Very few cases of C. burnetii infection of a vascular graft have been reported. All were diagnosed by serology. Case presentation We report the first case of Coxiella burnetii vascular graft infection diagnosed by broad-range PCR and discuss the diagnostic approaches and treatment strategies of chronic C. burnetii infection. Conclusion C. burnetii should be considered as etiological agent in patients with a vascular graft and fever, abdominal pain, and laboratory signs of inflammation, with or without exposure history. Broad-range PCR should be performed on culture-negative surgical samples in patients with suspected infection of vascular graft.